STEM- AND PROGENITOR-LIKE CELL CONTRIBUTION TO MALIGNANT ASTROCYTOMA HETEROGENEITY - Petritsch, Claudia (Oxford University Press, 2014)
BACKGROUND: Stem-like tumor propagating cells (TPCs) isolated from malignant astrocytoma (MA) are reportedly therapy-resistant. In contrast, progenitor-like TPCs with loss of asymmetric cell division (Cancer Cell. 20:328-40; 2011) are sensitive to temozolomide (Cancer Cell. 18:669-82; 2010). In a pediatric MA subset, an activating BRAFT1799A mutation leads to expression of hyperactivated BRafV600E kinase, and occurs with deletion of the cell cycle inhibitor CDKN2A (Cancer Res. 70:512-9; 2010). BRAFV600E-targeted therapies, including PLX4720, retard the growth of intracranial BRAFV600E MA xenografts (Clin. Cancer Res. 17:7595-604; 2011). Studies suggest that TPCs defined by current methods are not a homogeneous population and may contain subpopulations that respond differently to treatment. The divergent effects of targeted therapies on heterogeneous TPCs have yet to be explored. METHODS: Stem-like (CD133+) and progenitor-like (NG2+) cells were isolated from human MA cell lines and murine neurosphere cells with BRafV600E expression and Ink4a/Arf (CDKN2A) deletion. CD133+ and NG2+ cells labeled with proliferation markers were investigated for heterogeneity in cell cycle dynamics and division modes. Viability assays were used to determine PLX4720 IC50s, and RT-PCR was used to analyze cell cycle and polarity regulator gene expression. Pharmacological modulators of genes altered in NG2+ and CD133+ cells were tested alongside PLX4720 for anti-tumor efficacy in intracranial BRAFV600E MA xenografts. RESULTS: In murine CD133+ cells with BRafV600E expression and CDKN2A deletion, a low proliferation frequency and high rate of asymmetric division associate with reduced sensitivity to PLX4720-induced G1 arrest. Human CD133+ but not isogenic NG2+ cells have differential mRNA expression of G2-specific cell cycle regulators. Concurrently, CD133+ cells exhibit enhanced sensitivity to blockade of polo-like-kinase1 (PLK1), a cell cycle and polarity regulator. Results from ongoing analyses of the distinct proliferative capacities, cell cycle dynamics, cell division mode and responses to targeted BRafV600E and PLK1 inhibition of CD133+ and NG2+ MA cells will be presented. CONCLUSIONS: Our studies revealed that murine malignant astrocytoma TPCs are phenotypically and functionally heterogeneous. We further discovered a TPC-subpopulation specific therapy response, where CD133+ cells from malignant astrocytoma cell lines are more resistant to BRafV600E targeted inhibition but more sensitive to G2/M checkpoint kinase inhibition than NG2+ cells. This provides a potential mechanistic basis for the differential responses of stem and progenitor-like TPCs to treatment. Understanding why current treatment strategies preferentially target only certain cell-types will allow intelligent design of chemotherapeutic strategies with greater anti-tumor effects. SECONDARY CATEGORY: n/a.